👤

DAU COROANA!Descompuneti in factori:L a) [tex] x^{2} y^{2} -36 x^{2} + y^{4}-37 y^{2} +36 [/tex] b)[tex]25 x^{2} - x^{4}-25 y^{2} + x^{2} y^{2} [/tex] c)[tex] x^{3} y^{2} -100x- x^{2} y^{3}+100y+ x^{2} y^{2}z-100z [/tex] d) [tex] 4x^{2} y^{2} -( x^{2} + y^{2} - z^{2})^{2} [/tex] e) [tex] x^{4} +y^{4}-( x^{2} - y^{2} )+ x^{2} +y^{2}-(x-y)^{2} [/tex] f)[tex]( x^{2} -3) ( x^{2} -7)+4[/tex] g)[tex]( x^{2} -3)( x^{2} -6)+2[/tex] h)[tex] x^{4} +2x^{3}+2 x^{2} +2x+1 [/tex] i) [tex] x^{4} -3 x^{3} -3 x^{2} -3x-4 [/tex] j) [tex] x^{2} y^{4}z^{2}- x^{2} y^{2} z^{4}- x^{4} y^{2} z^{2} +x^{4}z^{4}[/tex] k)[tex]4(x-2) ^{2} +9+12(x-2) [/tex] l)[tex]9 x^{2} -4+4y^{4}+12xy[/tex]. Sa fie pe lung ca sa stiu cum ati rezolvat!

Răspuns :

a)[tex] x^{2} y^{2}+y^{4}-36x^{2}-36 y^{2}-y^{2}+36=[/tex][tex]y^{2}(x^{2}+ y^{2})-36( x^{2}+y^{2})-(y^{2}-36)=}(x^{2}+ y^{2})(y^{2}-36)-(y^{2}-36)[/tex][tex](y^{2}-36)(x^{2}+ y^{2}-1)=(y+6)(y-6)(x^{2}+ y^{2}-1)[/tex]
b)[tex] x^{2}(25- x^{2})-y^{2}(25- x^{2}) =( x^{2}-y^{2})(25- x^{2})= [/tex][tex](x+y)(x-y)(5+x)(5-x)[/tex]
c)[tex] x^{3}y^{2}-x^{2}y^{3}-100x+100y+x^{2}y^{2}z-100z= [/tex][tex] x^{2}y^{2}(x-y)-100(x-y)+z(x^{2}y^{2}-100)=[/tex][tex](x-y)( x^{2}y^{2}-100)+z( x^{2}y^{2}-100)=(x^{2}y^{2}-100)(x-y+z)=[/tex][tex](xy+10)(xy-10)(x-y+z)[/tex]
d)[tex](2xy- x^{2}-y^{2}+z^{2})(2xy+x^{2}+y^{2}-z^{2})[/tex]
f)([tex] x^{4}-7x^{2}-3x^{2}+21+4= x^{4}-10 x^{2}+25=( x^{2}-5)^{2}[/tex]
g)[tex] x^{4}-6x^{2}-3x^{2}+18+2=x^{4}-9x^{2}+20= x^{4}-4x^{2}-5(x^{2}-4)=[/tex][tex] x^{2}( x^{2}-4)-5( x^{2}-4)=(x^{2}-4)( x^{2}-5)=(x-2)(x+2)( x^{2}-5)[/tex]
h)[tex] (x^{4}+x^{3})+( x^{3}+x^{2})+(x^{2}+2x+1)=[/tex][tex]x^{3}(x+1)+ x^{2}(x+1)+(x+1)^{2}=(x+1)(x^{3}+x^{2}+x+1)[/tex]
i)[tex](x^{4}-1)-(3x^{3}+3x^{2})-(3x+3)=[/tex][tex](x^{2}-1)(x^{2}+1)-3x^{2}(x+1)-3(x+1)=[/tex][tex](x^{2}-1)(x^{2}+1)-(x+1)(3x^{2}-3)=[/tex][tex](x^{2}+1)(x^{2}-1)-3(x+1)(x^{2}-1)=(x^{2}-1)(x^{2}+1-3x-3)=[/tex][tex](x^{2}-1)(x^{2}-3x-2)[/tex]
j)[tex] x^{2}y^{4}z^{2}-x^{4}y^{2}z^{2}-(x^{2}y^{2}z^{4}-x^{4}z^{4})= [/tex][tex]y^{2}z^{2}(x^{2}y^{2}-x^{4})-z^{4}(x^{2}y^{2}-x^{4})=[/tex][tex](x^{2}y^{2}-x^{4})(y^{2}z^{2}-z^{4})=[/tex][tex] x^{2}z^{2}(y-x)(y+x)(y-z)(y+z)[/tex]
k)[tex] 4x^{2}-16x+16+9+12x-24=4x^{2}-4x+1=(2x-1)^{2}[/tex]
l)[tex]9x^{2}+12xy+4y^{2}-4=(3x+2y)^{2}-4=(3x+2y-2)(3x+2y+2)[/tex]